2021
DOI: 10.1108/jeas-12-2020-0208
|View full text |Cite
|
Sign up to set email alerts
|

Illicit financial outflows, informal sector size and domestic resource mobilization in selected African countries

Abstract: PurposeThe growth of both the informal sector and illicit financial outflows necessitated this study, in order to investigate how countries in Africa respond to these realities in terms of mobilization of domestic resources. These are the main motivation for the current study to the extant literature in conjunction with the adoption of employing second-generation econometric techniques which take into account cross-sectional dependence and country-specific heterogeneity.Design/methodology/approachThis study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…This result follows conventional knowledge and corroborates theoretical expectations. It also lends support to the studies of L epissier et al (2021), Thiao (2021) and Uzoechina et al (2021), who found that trade misinvoicing reduces government revenue and undermines domestic resource mobilization in developing countries.…”
Section: Effect Of Trade Misinvoicing On Domestic Resource Mobilizationsupporting
confidence: 75%
See 2 more Smart Citations
“…This result follows conventional knowledge and corroborates theoretical expectations. It also lends support to the studies of L epissier et al (2021), Thiao (2021) and Uzoechina et al (2021), who found that trade misinvoicing reduces government revenue and undermines domestic resource mobilization in developing countries.…”
Section: Effect Of Trade Misinvoicing On Domestic Resource Mobilizationsupporting
confidence: 75%
“…Empirical studies have shown that trade misinvoicing is a major deterrent to domestic resource mobilization (Lépissier et al , 2021; Thiao, 2021; Uzoechina et al , 2021), thus its coefficient is expected to be negative to depict its adverse impact on domestic resource mobilization in Nigeria. The inclusion of other explanatory variables is based on evidence of their effect on domestic resource mobilization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving and developing the financial sector in districts can alleviate financing constraints to some extent, providing investment opportunities for enterprises and encouraging the co-ordination advancement of two-way FDI foreign direct investment. Lastly, at the macro level, outbound direct investment and foreign direct investment should be controlled to curb illegal capital outflow and provide a better environment for optimizing the allocation of domestic resources [ 39 ].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The informal economy includes all economic activities not covered by law or formal arrangement (OECD/ILO, 2019). The informal economy is a highly persistent and ubiquitous phenomenon in many developing countries despite high economic growth in the past decades (Uzoechina et al ., 2023). While the informal economy accounts for one-fifth of the gross domestic product (GDP) and 16% of employment in the advanced economies, it accounts for one-third of the GDP and 70% of employment on average in emerging markets and developing economies (World Bank, 2020).…”
Section: Introductionmentioning
confidence: 99%